Training in Ultrasound to Determine Gestational Age in Low- and Middle- Income Countries: A Systematic Review - Alexandra C. Viner; Isioma D. Okolo; Jane E. Norman; Sarah J. Stock; Rebecca M. Reynolds (Frontiers Media S.A., 2022)
IntroductionEstablishing an accurate gestational age is essential for the optimum management of pregnancy, delivery and neonatal care, with improved estimates of gestational age considered a public health priority by the World Health Organization (WHO). Although ultrasound is considered the most precise method to achieve this, it is unavailable to many women in low- and middle- income countries (LMICs), where the lack of trained practitioners is considered a major barrier. This systematic review explores what initiatives have previously been undertaken to train staff to date pregnancies using ultrasound, which were successful and what barriers and facilitators influenced training.MethodsThe systematic review was conducted according to PRISMA guidelines and the protocol registered (PROSPERO CRD42019154619). Searches were last performed in July 2021. Studies were screened independently by two assessors, with data extracted by one and verified by the other. Both reviewers graded the methodological quality using the Mixed Methods Assessment Tool. Results were collated within prespecified domains, generating a narrative synthesis.Results25/1,262 studies were eligible for inclusion, all of which were programme evaluations. Eighteen were undertaken in Africa, three in South-East Asia, one in South America, and three across multiple sites, including those in Africa, Asia, and South America. Five programs specified criteria to pass, and within these 96% of trainees did so. Trainee follow up was undertaken in 18 studies. Ten met recommendations for training outlined by the International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) but only 1 met the current standards set by the WHO.DiscussionThis systematic review is the first to evaluate this topic and has uncovered major inconsistencies in the delivery and reporting of basic obstetric ultrasound training in LMICs, with the majority of programs not meeting minimum recommendations. By identifying these issues, we have highlighted key areas for improvement and made recommendations for reporting according to the RE-AIM framework. With an increasing focus on the importance of improving estimates of gestational age in LMICs, we believe these findings will be of significance to those seeking to develop and expand the provision of sustainable obstetric ultrasound in LMICs.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42019154619, PROSPERO CRD42019154619.